3(y-2)+6y=12

Simple and best practice solution for 3(y-2)+6y=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-2)+6y=12 equation:


Simplifying
3(y + -2) + 6y = 12

Reorder the terms:
3(-2 + y) + 6y = 12
(-2 * 3 + y * 3) + 6y = 12
(-6 + 3y) + 6y = 12

Combine like terms: 3y + 6y = 9y
-6 + 9y = 12

Solving
-6 + 9y = 12

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 9y = 12 + 6

Combine like terms: -6 + 6 = 0
0 + 9y = 12 + 6
9y = 12 + 6

Combine like terms: 12 + 6 = 18
9y = 18

Divide each side by '9'.
y = 2

Simplifying
y = 2

See similar equations:

| Y=150(2) | | x/3-10=9 | | 5u+18=8u | | -3/v=3 | | .12x=17000 | | 5b-9b=16 | | 8x+48=16 | | 37=15x-5x-3 | | 5u=14+3u | | n/24=5/8 | | -7=-5w+2(w-8) | | 3x+6(x+2)=12 | | (3m-2)(3m-2)=0 | | 11y=7y+20 | | 9(x+8)=-3x-12 | | 9a-10a=2 | | 6x-10x+15=4x-28-3 | | 5(x+4)-7x=18 | | 125x-(1500+12x)=0 | | 5(3r)+3r+r=508.21 | | 2(y-6)=3y-12-y | | 7x+12=2x+57 | | -7/9(x-15.6)=-9 | | -16x^2+72x+15=0 | | fx=6x+9 | | n=457 | | v(v+7)=0 | | x^2+25x+169=0 | | 5x-12=2x-8-7x | | 21=-x-35 | | x+(x*.16)=.041 | | -2x-6=4(x-3) |

Equations solver categories